Checkpoint ergonomics as a health and safety effort at work among women farmers - Dian Palupi Restuputri; Ilyas Masudin; Rahmad Wisnu Wardhana; Teguh Baroto; Arisna Arbiatul (Universitas Muhammadiyah Malang, 2023)
PT X is a company that works in the plantation sector, one of which is an orange plantation. In the process of harvesting lime leaves, there are 3 workstations and 4 work activities. Most of the work is done manually with a high workload and repetitive movements, causing musculoskeletal complaints. Workers complain of musculoskeletal disorders while working. During initial observation, there were complaints of pain in the neck, shoulders, arms, waist, thighs, and knees. Based on these problems, this study aims to analyze the factors that cause musculoskeletal disorders in the orange harvesting process. The method used to solve problems with partners is by using an ergonomic checklist and the PATH method to analyze three physical risk factors in the workplace. Based on the results of data processing using the PATH method, it was found that the biggest risk factors for injury were 45.53% soil hoeing, 42.39% harvesting and 12.08% grass cutting. The proposed improvements given after being analyzed using ergonomic checkpoints are: (1) reducing bending or squatting postures; and (2) providing protectors and covers for lawn mowers and handcarts and handles for tools for harvesting oranges. This proposed improvement is in accordance with Sustainable Development Goals number 3, namely Good Health and Wellbeing for all.